Association of carbamazepine-induced severe cutaneous drug reactions and HLA-B*1502 allele status, and dose and treatment duration in paediatric neurology patients in Singapore. Issue 6 (13th November 2013) - Chong, Kok Wee; Chan, Derrick W S; Cheung, Yin Bun; Ching, Leng Kee; Hie, Szu Liang; Thomas, Terrence; Ling, Simon; Tan, Ene Choo
Abstract : Objectives: To determine the association between severe cutaneous drug reactions (SCDR), HLA-B*1502 allelism, carbamazepine dose and treatment duration in a Singapore paediatric population. Method: Case–control study of SCDR with carbamazepine and HLA-B*1502. We recruited 32 cases, 5 with Steven Johnson Syndrome/Toxic Epidermolytic Necrolysis (SJS/TEN) (2 Chinese, 3 Malay), 6 with hypersensitivity syndrome (HSS) (5 Chinese, 1 Indian), 11 with minor drug reactions (9 Chinese, 2 Malay) and 10 controls (7 Chinese, 2 Malay, 1 Indian). HLA-B*1502 allelism was assayed. HLA-B*1502 status and the type of drug reaction were compared using univariate analysis. The time-span from treatment onset to reaction and the dose-time to reaction association in the 3 groups were analysed. Results: HLA-B*1502 was positive in: 5/5 (SJS/TEN), 0/6 (HSS), 1/11 (minor drug reactions) and 1/10 controls. OR for SJS/TEN in HLA-B*1502-positive patients relative to that in HLA-B*1502-negative patients was estimated by exact logistic regression to be 27.20 (95% CI 2.67 to ∞). Median treatment duration (days) until allergic reactions was 12 (range 11–13), 16 (range 10–37) and 11 (range 0–63) for SJS/TEN, HSS and minor drug reactions, respectively. Median dose at onset of reactions was 6.2 mg/kg/day (range 4.6–7.4), 9.8 mg/kg/day (range 7.7–12.2) and 6.7 mg/kg/day (range 3.6–20.0) for the 3 groups, respectively. Conclusions: HLA-B*1502 positivity increases the odds of carbamazepine-induced SCDR in Singapore children of Chinese and Malay ethnicity. Adverse drug reactions to carbamazepine occurred within 2 weeks and at low doses.